المنهج الفقهي عند محمد عز الدين عباسي السوفي (ت:1435هـ) - مهاوه, الطاهر (University of Eloued جامعة الوادي, 2021)
هذه الدراسة الموسومة بـــ: "المنهج الفقهي عند محمـد عز الدين عباسي السوفي (ت:1435ه)"، تجلّت أهميتها في كوْنها متعلقة بأحد أعلام وفقهاء وادي سوف وهو الشيخ محمد عز الدين عباسي الذي كان متبصّرًا بمقتضيات العصر؛ فربط بين النصوص والثوابت والمتغيرات، والمقاصد والعلل، مراعيًا في ذلك مصلحة العباد والبلاد، فكان الإشكال الرئيس الذي سَعَتْ للإجابة عنه: ما هو المنهج الفقهي الذي سلكه الشيخ في فتاويه المطبوعة (تحفة السالك) التي تمثّل جُلّ إنتاجه العلمي؟ حاولت الدراسة الإجابة عن ذلك من خلال مبحث تمهيدي للتعريف بمنطقة وادي سوف وعلاقتها بالشيخ عباسي، ثم خمسة فصول متكاملة؛ أوّلها خُصّص للتعريف العام بالشيخ، وثانيها لدراسة وتقييم فتاواه (تحفة السالك)، وثالثها لماهية المنهج الفقهي وموضع الشيخ منه باعتباره مفتيًا، ورابعها لآداب وطريقة وضوابط الفتوى عنده من خلال (تحفة السالك)، وأخيرًا خامسها للأبعاد الحضارية لمنهجه الفقهي من خلال التحفة ذاتها. ثمّ خُتمت الدراسة برصْد مجموعة من النّتائج؛ أهمّها: أن المنهج الفقهي للشيخ محمد عز الدين عباسي يقوم على الإفتاء بالمذهب المالكي؛ وذلك من خلال القول المشهور للمذهب، وذكْر نصوص فقهائه والاستشهاد بهم، مع عدم التعصب للمذهب كالفتوى بالخروج من الخلاف، وخلاف الأوْلى. كما تُوّجت الخاتمة ببعض التوصيات التي رأى الباحث أنها تزيد في خدمة الموضوع مستقبلاً، وتُعَدُّ إسهامًا فاعلاً في سدّ الحاجة في المكتبة الفقهية؛ والتي من بينها: إعادة طبْع مجمَع فقه الشيخ عباسي؛ كتاب (تحفة السالك) محقّقًا تحقيقًا علميًّا؛ حتى يخرج في حُلّة تليق بالشيخ وفتاويه، مع اقتراح إدراج مقياس خاصٍّ بمناهج الفقهاء في الدراسات الشرعية ضمن المقررات الجامعية. This study, tagged with: “The Jurisprudence Method of Muhammad Izz al-Din Abbasi al-Sufi (d .: 1435 AH),” was evident in its importance as it relates to one of the most prominent scholars and jurists of Wadi Suf, Sheikh Muhammad Izz al-Din Abbasi, who was perceptive of the requirements of the era. So he linked the texts, constants and variables, objectives and justifications, taking into account the interest of the people and the country, so the main problem that I sought to answer was: What is the jurisprudential approach that the sheikh followed in his printed fatwas (Tuhfat al-Salek) that represent the bulk of his scientific production? The study attempted to answer this through an introductory study to introduce the region of Wadi Souf and its relationship with Sheikh Abbasi, then five integrated chapters. The first was devoted to a general definition of the Sheikh. The second was devoted to studying and evaluating his fatwas (Tuhfat al-Salek). The third of which was the essence of the jurisprudential approach and the position of the Sheikh from him as a mufti. The fourth of which was for the etiquette, method and controls of his fatwa through (Tuhfat al-Salik). Finally the fifth was for the cultural dimensions of his jurisprudential approach through the masterpiece itself. The study was then concluded by monitoring a set of results. The most important of them are: The jurisprudential curriculum of Sheikh Muhammad Izz al-Din Abbasi is based on the fatwas of the Maliki school of thought This is through the well-known saying of the doctrine, mentioning the texts of its jurisprudence and citing them, without fanaticism to the doctrine, such as the fatwa to get out of the disagreement, and disagree with the first. The conclusion also culminated in some recommendations that the researcher believed would increase the service of the topic in the future, and constitute an effective contribution to filling the need in the jurisprudence library. Among them: Reprinting the Sheikh Abbasi Fiqh Academy. Book (Tuhfat Al-Salek), a scientific investigator. In order for him to come out in a manner befitting the Sheikh and his fatwas, with a suggestion to include a standard for the curricula of jurists in Sharia studies within university courses.
أطروحة دكتوراه في العلوم الإسلامية تخصص الفقه وأصوله
Keywords: المنهج الفقهي – الشيخ عباسي – تحفة السالك; Fiqh Approach - Sheikh Abbasi - Tuhfat Al-Salek